Assessing the acute effects of accentuated eccentric contrast training on vertical jump using wireless dual force plates in young basketball players - Clemente-Benedicto, J.; García-Sánchez, C.; González-García, J.; Alonso-Aubin, D.; Nieto-Acevedo, R. (Sensors, 2026)
Background: Basketball performance depends strongly on physical preparation. A novel approach is accentuated eccentric loading within contrast training, though its acute effects using dumbbells remain underexplored. Methods: Twelve youth basketball players (age = 16.0 ± 0.3 years; body mass = 81.5 ± 7.6 kg) completed three sessions with dumbbell loads equivalent to 15%, 30% and 45% BW. CMJ performance was measured using dual wireless dual force plates. Assessments were conducted before the protocol and at 3, 9, and 15 min post intervention. Subjective responses were collected via wellness, RPE and readiness questionnaires. A two-way repeated measures ANOVA with Bonferroni corrections was applied, and the significance level was set to a = 0.05. Results: Significant decreases in jump height (p = 0.010) and average propulsive power (p = 0.005) were observed in the 45% BW condition at 3 and 9 min. Jump momentum decreased significantly at 30% and 45% BW at 3 and 9 min (p = 0.010; p = 0.033). No significant differences were detected in other CMJ force-time metrics (p > 0.05). Conclusions: Dumbbell-loaded CMJs as an accentuated eccentric loading contrast exercise did not produce generalized improvements but induced acute decreases at higher loads. However, they may still be useful in individual cases for athletes with favorable responses after monitoring.